Harnessing the Power of Purun Tikus (Eleocharis dulcis) to Reduce Toxic Heavy Metals in Wetlands - Mazidah; Suheryanto, Suheryanto; Sarno, Sarno (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
The escalating contamination of heavy metals such as lead (Pb), zinc (Zn), and copper (Cu) in wetland ecosystems poses a significant threat to environmental integrity and public health. This study aims to assess the phytoremediation potential of purun tikus (Eleocharis dulcis) for the accumulation and reduction of these heavy metals in contaminated sediment and water matrices. An experimental approach was employed wherein purun tikus specimens were cultivated for 20 days in media artificially contaminated with varying concentrations of Pb (5, 10, 15 mg/L), Zn (80, 90, 100 mg/L), and Cu (80, 90, 100 mg/L). There was no significant difference (p > 0.05) in the accumulation of heavy metals Pb, Zn, and Cu in the roots, stems, and leaves of purun plants between treatment times of 5, 10, 15, and 20 days. The duration of treatment did not significantly affect the ability of purun plants to accumulate these heavy metals. The descriptive differences seen although not statistically significant are likely due to the small sample size and high variability of the data. The highest removal efficiencies were observed for Pb in stems (95.97%), Zn in roots (81.59%), and Cu in stems (66.10%). These findings indicate that purun tikus exhibits selective metal uptake and distribution mechanisms coupled with high tolerance to heavy metal stress, affirming its efficacy as a phytoremediator for rehabilitating heavy metal-contaminated wetlands and supporting sustainable ecosystem management.